2009
DOI: 10.1002/art.24844
|View full text |Cite
|
Sign up to set email alerts
|

Human inflammatory synovial fibroblasts induce enhanced myeloid cell recruitment and angiogenesis through a hypoxia‐inducible transcription factor 1α/vascular endothelial growth factor–mediated pathway in immunodeficient mice

Abstract: Objective. Hyperplasia and phenotypic changes in fibroblasts are often observed in chronic inflammatory lesions, and yet the autonomous pathogenic contribution of these changes is uncertain. The purpose of this study was to analyze the intrinsic ability of fibroblasts from chronically inflamed synovial tissue to drive cell recruitment and angiogenesis.Methods. Fibroblasts from patients with rheumatoid arthritis (RA) or osteoarthritis (OA), as well as fibroblasts from healthy synovial tissue and healthy skin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 105 publications
3
55
0
Order By: Relevance
“…To define low and high inflammatory subtypes, we analysed gene identities in the subclusters (A to E) displaying clearly differential gene expression between subgroups (figure 5B). Consistent with prior studies, group III could be classified as a high inflammatory subtype based on significantly increased expression of genes involved in chemotaxis, angiogenesis and transforming growth factor β/activin A pathways 10 25 26…”
Section: Resultssupporting
confidence: 78%
“…To define low and high inflammatory subtypes, we analysed gene identities in the subclusters (A to E) displaying clearly differential gene expression between subgroups (figure 5B). Consistent with prior studies, group III could be classified as a high inflammatory subtype based on significantly increased expression of genes involved in chemotaxis, angiogenesis and transforming growth factor β/activin A pathways 10 25 26…”
Section: Resultssupporting
confidence: 78%
“…Because RA synoviums contain high numbers of inflammatory cells (e.g., macrophages) compared with OA synoviums, higher levels of ER signature in RA synoviums could be just a result of higher numbers of macrophages expressing UPR genes. To address this issue, we freshly isolated OA macrophages from OA ( Reddy et al, 2003;Misra et al, 2005Misra et al, , 2006Pyrko et al, 2007). Evidence is also emerging that GRP78 protects many tissues and organs under ER stress (Wang et al, 2010;Pfaffenbach and Lee, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…16,17,20,23,40 The role of CXCL12 in cartilage destruction was further supported by in vivo experiments, which showed that CXCL12 antagonists inhibit fibroblast-induced cell infiltration in immunodeficient mice. 41 CXCL12 can signal via CXCR4 and CXCR7. Expression of CXCR4 has been detected in synovium of healthy individuals as well as in OA and RA patients.…”
Section: Dna Methylation Regulates the Expression Of Cxcl12 E Karouzamentioning
confidence: 99%